Crosslinked poly(norbornene-dicarboximide)s as electro-optic chromophore hosts. (December 2017) - Spring, Andrew M.; Qiu, Feng; Hong, Jianxun; Bannaron, Alisa; Kashino, Tsubasa; Kikuchi, Takamasa; Ozawa, Masaaki; Nawata, Hideyuki; Odoi, Keisuke; Yokoyama, Shiyoshi
Graphical abstract: Highlights: A series of soluble crosslinked polymers have been prepared and utilized as FTC chromophore hosts. Crosslinks could be systematically increased until an insoluble gel resulted by the addition of a bifunctional NDI monomer. Crosslinking evidence was provided by large increases in the polymer Mw, PDIs and viscosities. Thermal properties such as the Tg and Td were unaffected by the degree of crosslinking. An increased degree of crosslinking enhanced the polling efficiency of the EO materials. Abstract: A series of crosslinked poly(norbornene-dicarboximide)s have been prepared by ring opening metathesis polymerization. Increasing quantities of a bifunctional norbornene-dicarboximide crosslinker was doped into a high Tg cyclohexyl-substituted norbornene-dicarboximide monomer before polymerization. The wt% of the crosslinker was increased from 0.00 to 4.40 wt%, after which the polymers became gelated. Polymer molecular weights increased drastically from 23, 500 to 2, 135, 000 g/mol, the polydispersities increased from 1.18 to 73.47 and the viscosities increased from 5.27 to 538.7 mPa·s as the wt% of the crosslinker was increased. The trans : cis vinylene ratio remained constant at 1:0.18 as well as the Tg and Td with average values of 210 °C and 392 °C being measured. Five of the crosslinked polymers and the reference homopolymer were utilized as hosts for the high activity tert -butyldiphenylsilyl substituted FTC chromophore guest. The polymer host containing 1.96 wt% crosslinker was found to have a maximum r33 of 78 pm/V when polled at 150 °C with an electric field strength of 100 V/μm. The r33 increased linearly from 63 to 78 pm/V as the wt% of the crosslinker was increased from 0.00  to 1.96 wt%. The thermal and temporal stability was found to increase slightly with the 0.00 wt% polymer exhibiting a stability of 77%, while the 1.96 wt% polymer exhibited a stability of 79% when both were heated to 85 °C and aged for 500 h in air.